The Influence of Work Motivation, Work Discipline on Performance Through Visionary Leadership - Muskinta; Gus Andri; Didi Aryadi (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
The purpose of this study was to determine the effect of work motivation and work discipline on performance through visionary leadership as a mediating variable. Quantitative method with a survey approach. The population of 208 people in the village government and a sample of 208 people were taken using a non-probability sampling technique with a census method because the population is relatively small, this sampling aims to simplify data collection. The data collection technique used a questionnaire. The PLS-SEM data analysis technique used the SmartPLS 4 application. The results of the study found that work motivation, work discipline and visionary leadership have a positive and significant effect on the performance of village officials. Work motivation and discipline have a positive and significant effect on visionary leadership. Visionary leadership has the ability to mediate work motivation, work discipline on the performance of village officials. The results of the determination coefficient test are in the form of an Adjusted R-square value of 0.859. This means that work motivation and work discipline in explaining visionary leadership are 85.9% (high). Furthermore, the Adjusted R-square value is 0.808. This means that work motivation and work discipline can explain performance by 80.8% (high). These findings suggest that when village officials have high motivation and work discipline, their performance will improve. Visionary leadership also plays a role in strengthening work motivation and discipline, influencing the performance of village officials. Therefore, work motivation, work discipline, and visionary leadership are important for realizing good village governance.